2014
DOI: 10.1136/bmjopen-2014-004783
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of embarrassment in gynaecological screening: a qualitative study from the ASPIRE cervical cancer screening project in Uganda

Abstract: ObjectiveTo define embarrassment and develop an understanding of the role of embarrassment in relation to cervical cancer screening and self-collected human papillomavirus (HPV) DNA testing in Uganda.DesignCross-sectional, qualitative study using semistructured one-to-one interviews and focus groups.Participants6 key-informant health workers and 16 local women, purposively sampled. Key informant inclusion criteria: Ugandan members of the project team. Focus group inclusion criteria: woman age 30–69 years, Luga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(97 citation statements)
references
References 41 publications
3
73
1
1
Order By: Relevance
“…It is worth noting that lower prevalence of self‐identified chronic disease does not necessarily reflect true disease status in these women, as some women may be undiagnosed as a result of lack of access to health services or avoid health care for other reasons. Although the demographic/behavioural risk factors captured in this study do not appear to explain this, other studies from ASPIRE have identified lack of perceived risk, knowledge of health issues, embarrassment and competing priorities as factors that contribute to engagement with cervical cancer screening .…”
Section: Discussioncontrasting
confidence: 60%
“…It is worth noting that lower prevalence of self‐identified chronic disease does not necessarily reflect true disease status in these women, as some women may be undiagnosed as a result of lack of access to health services or avoid health care for other reasons. Although the demographic/behavioural risk factors captured in this study do not appear to explain this, other studies from ASPIRE have identified lack of perceived risk, knowledge of health issues, embarrassment and competing priorities as factors that contribute to engagement with cervical cancer screening .…”
Section: Discussioncontrasting
confidence: 60%
“…Moderate levels of cancer worry have predicted breast cancer screening in high-risk women (Diefenbach, Miller, & Daly, 1999; Zhang et al, 2012). Cancer worry about the results of cervical cancer screening was also identified as an important psychosocial barrier to the screening process in an international qualitative study (Teng et al, 2014). Lung cancer worry may be an important psychological variable in the decision to screen or not in lung cancer.…”
Section: Literature Review and Empirical And/or Theoretical Support Fmentioning
confidence: 99%
“…Breasts are also strongly related to maternal caring via breast‐feeding of infants. At the same time, female genitals (especially the vagina and internal organs) are still seen as “unclean” (associated with excretory functions) and a taboo topic for social settings . Patients may experience higher rates of distress after being diagnosed with a cancer that is associated with sexually transmitted diseases (cervical and vulvar).…”
Section: Introductionmentioning
confidence: 99%
“…(associated with excretory functions) and a taboo topic for social settings. 15,16 Patients may experience higher rates of distress after being diagnosed with a cancer that is associated with sexually transmitted diseases (cervical and vulvar). In addition, GYN patients deal with sexual dysfunction and loss of reproductive ability.…”
mentioning
confidence: 99%